TADALAFIL AS AN AGENT OF PHARMACOLOGICAL PRECONDITIONING IN ISCHEMIC – REPERFUSION BRAIN INJURY - Olga Martynova (Research Results in Pharmacology, 2017)
Introduction: Ischemic stroke or cerebral infarction is the main pathology among severe forms of vascular lesions of the brain. One of the more effective non-medicamental methods of treatment is pharmacological preconditioning. Pharmacological neuroprotection is one of the treatment areas to reduce the damage in ischemic stroke and other modifications of brain ischemia. Therefore, the development and introduction of new pharmacological agents that can reduce the degree of ischemic-reperfusion injury of the brain, remains one of the major challenges of modern medicine. The most promising to explore, from our point of view, is a PDE-5 inhibitor.